THE EFFECT OF TIME TOKEN STRATEGY ON THE EIGHTH GRADE STUDENT SPEAKING SKILLS AT SMP AL-IJTIHAD 2 KUTABARU - Siti Rismiyatul Hidayah; Aidil Syah Putra; Yudhie Indra Gunawan (Universitas Muhammadiyah Tangerang, 2021)
This study aims to determine the effect of time token strategy to improve students' speaking skills. This research method is a quasi-experimental method with a non-equivalent design. The study population was the students of SMP Al-Ijtihad 2 Kutabaru. There are four classes consisting of class VIII A, VIII B, VIII C, and VIII D. Consisting of 33 VIII A students, 32 VIII B students, 33 VIII C students, and 33 VIII students. The total population is 131 students. The researcher took several students to be the research sample. Purposive Sampling was chosen as the sampling technique in this study. Consisting of 65 students, class VIII B as the experiment class and VIII C as the control class. The two classes were given different treatment. The experimental class was taught using Time Token Strategy while the control class was taught using conventional methods. The study was started by giving pre-test, treatment, and post-test to both classes. The data from the test were analyzed using the t-test formula at a significant level of 5% (0.05). The results of the pre-test analysis using the t-test formula obtained data that shows tcount 1.934461139 is smaller than ttable 2.00, which means that H0 is accepted. Meanwhile, the post-test results show that tcount 2.64672013 is betterr than ttable 2.00, which means H1 is accepted. Based on the research conducted, it proves that there are significant differences in the results of learning speaking using the Time Token Strategy at SMP Al-Ijtihad 2 Kutabaru, and the Time Token Strategy can make students more active in the learning process.Keywords: Strategy Time Token, Speaking Skill.